2011
DOI: 10.1519/jsc.0b013e318212e415
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Between-Set Rest Intervals on the Oxygen Uptake During and After Resistance Exercise Sessions Performed with Large- and Small-Muscle Mass

Abstract: Between-set rest intervals (RIs) may influence accumulated fatigue, work volume, and therefore oxygen uptake (VO2) and energy expenditure (EE) during resistance training. The study investigated the effects of different RIs on VO2 and EE in resistance exercises performed with multiple sets and recruiting large and small-muscle mass. Ten healthy men performed 4 randomized protocols (5 sets of 10 repetitions with 15 repetition maximum workloads in either horizontal leg press [LP] or chest fly [CF] with an RI of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 15 publications
0
44
0
1
Order By: Relevance
“…Many studies have shown the effect of acute variables of WT on the EE, such as performance velocity 14 , rest interval 21 , load intensity 14 , number of sets 22 , number of repetitions 18 , training volume 23 and muscular mass involved 24 . Thus, it is worth mentioning that in the present study the experimental sessions were identical compared with the training variables, the only difference between the methods was the training design.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown the effect of acute variables of WT on the EE, such as performance velocity 14 , rest interval 21 , load intensity 14 , number of sets 22 , number of repetitions 18 , training volume 23 and muscular mass involved 24 . Thus, it is worth mentioning that in the present study the experimental sessions were identical compared with the training variables, the only difference between the methods was the training design.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally many studies discarded the �rst minutes of the EPOC, therefore overlooking its rapid phase even though approximately 1⁄3 of the total VO 2 recovery takes place during this period [39]. In the present paper, only �ve studies [16,22,26,27,34] assessed the EPOC immediately aer the end of RT.…”
Section: Methodological Issues In Epoc Analysismentioning
confidence: 88%
“…It is therefore important to standardize the rest intervals between sets and exercises to prevent assessment bias: short intervals result in high EPOC, but less EE within the exercise session. On the other hand, longer intervals result in lower EPOC, but greater EE during the session [16,34].…”
Section: Methodological Issues In Epoc Analysismentioning
confidence: 95%
See 2 more Smart Citations